Analysis of the State Management System for the Development of Cities and Urban Agglomerations - Akhmetova, A.; Nakipova, G.; Mussatayeva, A.; Omarova, A.; Kunyazova, S.; Gusmanova, Z. (Montenegrin Journal of Economics, 2024)
Urbanization plays an important role in the development of the country, forming urban centers of economic activity, innovation and socio-cultural events. The study allows determining how effectively the state is manag-ing this process, as well as what changes and improvements can improve the quality of urban life. The study of public management of the urbaniza-tion process in Kazakhstan will identify problems, good practices and po-tential for improving the management of urban development, which ulti-mately can help improve the quality of life of citizens and ensure the sus-tainable development of the country. The relevance of the study lies in the fact that the analysis of public management of the urbanization process in Kazakhstan will identify problems, successful practices and potential for improving the management of urban development, which ultimately can help improve the quality of life of citizens and ensure the sustainable development of the country. The purpose of the study is to evaluate the effectiveness and improve public administration of the urbanization pro-cess in Kazakhstan to ensure sustainable and high-quality urban develop-ment and improve the quality of life of citizens.
Keywords: Strategic analysis; regional youth policy; regional personnel policy; regional staffing; strategic planning; regional economy